Empowerment of Cassava Leaf Silkworm Cultivation Groups Through Processing of Ceara Rubber Tree (Manihot Glaziovii) as Local Food Potential - Subrata, Arsyad Cahya; Ibdal, Ibdal; Sudarmini, Sudarmini; Suharto, Totok Eka; Putranti, Deslaely; Rahmawan, Jihad; Aska, Ghoniyun Nisa Uskhulil; Hidayah, Laelatul (Indonesia Berdaya, 2025)
Food security has become an increasingly urgent global issue as the impact of climate change and the global food crisis intensify. Indonesia, as an agrarian country, has great potential to strengthen its food system to be self-sufficient and sustainable, one of which is through the empowerment of local farmer groups. This article discusses efforts to enhance food security through agricultural product diversification by leveraging untapped local potential, specifically the processing of rubber tree (Manihot glaziovii) tuber skins. Empowerment activities were conducted with the Sutra Alam Gunung Sewu group in Gunungkidul Regency, DIY, which had previously only utilized the plant's leaves as silkworm feed. The tubers and bark of this tree, which are nutrient-rich but contain high levels of cyanide acid, have the potential to be developed as an alternative food source if processed properly. The empowerment program was implemented to enhance the group's capacity to process the tuber bark into useful products. Evaluation was conducted using pre-test and post-test instruments to measure improvements in members' knowledge and skills. The results showed a 120% increase in general knowledge and an 84% increase in understanding of information regarding the potential of local food and the processing of risky materials into safe consumption. This initiative contributes to food diversification and the economic empowerment of local communities in supporting national food security.